2003
DOI: 10.1021/jf034225f
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal and Adulticidal Effects of Eugenia caryophyllata Bud and Leaf Oil Compounds on Pediculus capitis

Abstract: The toxicity of Eugenia caryophyllata bud and leaf oil-derived compounds (acetyleugenol, beta-caryophyllene, eugenol, alpha-humulene, and methyl salicylate) and congeners of eugenol (isoeugenol and methyleugenol) against eggs and females of Pediculus capitis was examined using direct contact application and fumigation methods and compared with those of the widely used delta-phenothrin and pyrethrum. In a filter paper diffusion bioassay with female P. capitis, the pediculicidal activity of the Eugenia bud and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 21 publications
2
116
0
11
Order By: Relevance
“…The inhibitory activity exhibited by Syzygium aromaticum oil against the test organisms in this research is due to the presence of several constituents such as eugenol, betacaryophyllene, limonene, alpha terpinolene (Chaieb et al, 2007), acetyl eugenol, methyl salicylate, iso-eugenol, methyl-eugenol, phenylacetic acid, salicyclic acid, protocatechuic acid, p-hydroxybenzoic acid, eugenin, eugenitin (Yang et al, 2003), phenolic compounds (kaempferol, rhamnetin, isorhamnetin, myricetin, quercetin, gallic acid, caffeic acid and syringic acid) (Table II) respectively (Cai and Wu, 1996). The broad spectrum antimicrobial activity exhibited by Syzygium aromaticum oil and crude extract agrees with the reports of Park et al, (2007) and Fu et al, (2007) that reported potent antifungal and antibacterial effects of Syzygium aromaticum on microorganisms due to its mechanism of action which include denaturation of proteins and reaction with cell membrane phospholipids thus changing the membrane permeability of the microorganism.…”
Section: Discussionmentioning
confidence: 81%
“…The inhibitory activity exhibited by Syzygium aromaticum oil against the test organisms in this research is due to the presence of several constituents such as eugenol, betacaryophyllene, limonene, alpha terpinolene (Chaieb et al, 2007), acetyl eugenol, methyl salicylate, iso-eugenol, methyl-eugenol, phenylacetic acid, salicyclic acid, protocatechuic acid, p-hydroxybenzoic acid, eugenin, eugenitin (Yang et al, 2003), phenolic compounds (kaempferol, rhamnetin, isorhamnetin, myricetin, quercetin, gallic acid, caffeic acid and syringic acid) (Table II) respectively (Cai and Wu, 1996). The broad spectrum antimicrobial activity exhibited by Syzygium aromaticum oil and crude extract agrees with the reports of Park et al, (2007) and Fu et al, (2007) that reported potent antifungal and antibacterial effects of Syzygium aromaticum on microorganisms due to its mechanism of action which include denaturation of proteins and reaction with cell membrane phospholipids thus changing the membrane permeability of the microorganism.…”
Section: Discussionmentioning
confidence: 81%
“…[60][61][62][63] While, M. fragrans (E. aromatica) contains: eugenol, eugenyl acetate, cariofilen β-caryophyllene, 1,8-Cineole and -Cadinene which produce characteristic smell and insecticidal activity [64][65][66][67] which is responsible for the sharp, peppery taste, characteristic smell, insecticidal and biological activity of A. melegueta and M. fragrans (E. aromatica). [17][18][19][20][21][22][23][60][61][62][63][64][65][66][67][68] …”
Section: Discussionmentioning
confidence: 99%
“…Estos fueron "toxicidad en fase vapor" y "toxicidad por inmersión". Para evaluar la seguridad se efectúo la "toxicidad sobre tejido" (ensayo HET-CAM) [12][13][14][15] . Como control se usó deltametrina 0,02 g y piperonil butóxido 2,5 g, shampoo.…”
Section: Bioensayos Y Estudios De Toxicidad In Vitro De La Formulaciónunclassified